IN-VITRO DETACHED LEAF ASSAY OF HOST-MEDIATED RNAi LINES CARRYING PHYTOPHTHORA INFESTANS AVR3A EFFECTOR GENE FOR LATE BLIGHT RESISTANCE - Sanju, Suman; Thakur, Aditi; Siddappa, Sundaresha; Sharma, Sanjeev; Shukla, Pradeep Kumar; Srivastava, Nidhi; Pattanayak, Debasis; Singh, B P (Potato Journal, 2016)
Phytophthora infestans, the causal organism of potato late blight adversely affects the quality as well as quantity of the potato crop. Late blight is the most dreaded biotic stress of potato till date. Although, a number of management strategies have been developed for the effective management of the disease but the fast evolving virulent strains of P. infestans still pose a challenge. The RXLR effector gene Avr3a from P. infestans has been silenced through small interfering RNA (siRNA) and artificial micro RNA (amiRNA) techniques, as Avr3a has been demonstrated to be essential factor for virulence in P. infestans. Phenotyping of Kufri Khyati and Kufri Pukhraj lines of potato developed through siRNA and amiRNA for late blight resistance was undertaken using detached leaf assay. The siRNA derived lines Kufri Khyati 1037 and Kufri Khyati 1129 and amiRNA derived line Kufri Khyati 2.1358 exhibited less lesion area as well as spore production and categorized as moderately resistant. Also, the reduced expression of Avr3a transcript in the siRNA derived lines Kufri Khyati 1037 and Kufri Khyati 1129 and amiRNA derived line Kufri Khyati 2.1358 coincided with the less disease severity in the leaves of transformed plants. Although both techniques of RNAi had remarkable effect on the pathogenicity of the gene Avr3a still siRNA mediated technique of silencing performed better than amiRNA mediated gene silencing when tested through detached leaf assay.